Preeclampsia and eclampsia echoes of a presentation. - Pacheco Romero, José (2015)
We still do not know the etiology of preeclampsia-eclampsia. Even the name -used induced hypertension pregnancy in the last decade does not fit the pathophysiological changes that occur in the disease. So, today we know that hypertension is an important sign, a consequence of the disease and not the cause, and possibly appears to compensate for the reduced blood flow to the feto1. In some women, compensation cracks and severe multisystem disease it occurs, resulting in pregnancy induced hypertension and preeclampsia.